Reformasi Administrasi dan Paradoks Demokrasi - Margono, Subando Agus (Jurnal Ilmu Sosial dan Ilmu Politik, 2005)
Democratization in Indonesia has been manipulated through various instruments of administrative reform. The Indonesian bureaucrats, consequently, faces up the pressures from the political elites who have then new comfort space in bureaucratic government. This paper describes the dynamics of political interaction of the bureaucrats within the new government of Indonesia.